2019
DOI: 10.1097/mat.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption does not Have Influence on Hemolysis During Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass (CPB) induces hemolysis, which manifests as plasma free hemoglobin. We investigated in a post hoc analysis of a single-center, blinded, controlled study whether the use of a novel hemoadsorption device (CytoSorb, CytoSorbents Europe GmbH, Berlin, Germany) affects hemolysis during CPB. A total of 35 patients undergoing elective CPB surgery with an expected CPB duration of more than 120 min were included in the analysis. The hemoadsorption device was used in 17 patients (intervention group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Next, we aimed to assess the utility of circulating microvesicles and apoptotic bodies as indicators of inflammation and hemolysis. In our previous studies [4,5], we found no effect on inflammation and hemolysis between patients treated with hemoadsorption compared to the control group, although a greater decrease in haptoglobin levels on postoperative day 1 was observed. Using correlation analysis, we did not detect significant correlations between MV subpopulations, haptoglobin, free hemoglobin, bilirubin, lactate dehydrogenase and C-reactive protein (Fig.…”
Section: Vesicle Counts Correlate With High-motility Group Box-1 Levelscontrasting
confidence: 49%
See 2 more Smart Citations
“…Next, we aimed to assess the utility of circulating microvesicles and apoptotic bodies as indicators of inflammation and hemolysis. In our previous studies [4,5], we found no effect on inflammation and hemolysis between patients treated with hemoadsorption compared to the control group, although a greater decrease in haptoglobin levels on postoperative day 1 was observed. Using correlation analysis, we did not detect significant correlations between MV subpopulations, haptoglobin, free hemoglobin, bilirubin, lactate dehydrogenase and C-reactive protein (Fig.…”
Section: Vesicle Counts Correlate With High-motility Group Box-1 Levelscontrasting
confidence: 49%
“…High mechanical stress, different blood flow and pressure conditions, surface activation and cardiotomy suctioning can lead to excessive hemolysis during the perioperative course [18]. In our previous study [5], no effect on hemolysis between patients treated with hemoadsorption compared to the control group was found. However, a greater decrease in haptoglobin levels and an increase in lactate dehydrogenase on POD 1 in the control group was observed, which may be an indicator for free hemoglobin adsorption in the intervention group.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There are one systematic review [ 67 ], one multicenter RCT [ 68 ], five single-center RCTs (one ongoing) [ 69 73 ], and three related published studies [ 74 76 ]. In the systematic review published in 2021, except two RCTs investigating the application of extracorporeal cytokine adsorption therapy as a therapeutic add-on treatment in sepsis or septic shock, the other five RCTs investigated the application of CytoSorb as a preventive measure in cardiac surgery from 2016 to 2019.…”
Section: Evidence For the Application Of Cytosorb During Cpb Surgerymentioning
confidence: 99%
“…Interestingly, although Bernardi et al [20] did not find a difference in IL-1b, IL-6, IL-18, and TNF-α levels in their 37-patients pilot RCT, they reported significantly higher levels of the anti-inflammatory IL-10 48 h after post-CPB. Again, there was no difference in clinical outcomes.…”
Section: Removal Of Pro-inflammatory Mediators and Other Substancesmentioning
confidence: 77%